Kann der Plastische Chirurg Leiter des Departments für Chirurgie an einer Universitätsklinik sein?……..Das funktioniert wirklich? - Neumeister, M. W. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2016)
There is significant responsibility in being a Department of Surgery Chairman within a medical school. The Chairman is appointed by the Dean of Medicine to lead surgery in a path that serves the mission of the school. The Department of Surgery Chairman is charged with facilitating the academic, operational, and programmatic surgical initiatives of the School of Medicine. Traditionally the Chairman of Surgery has been a general surgeon but now our educational and clinical experiences have changed making traditional leadership less intuitive. Plastic surgeons appointed as current Chairman of the Department of Surgery are rare in the United States. Whereas, general surgeons may have less interaction with other surgical sub-specialties today, Plastic surgeons have more interaction crossing all disciplines of surgery. Innovation and creativity that defines our discipline, seems to fit well with Department leadership where strategic planning, vision and curriculum development, and the pursuit of academic and clinical quality remain core essentials to plastic surgery. This article is an editorial of my philosophy as a plastic surgeon leading a Department of Surgery.
Keywords: plastic surgery; department; division; general surgery; independence